Mechanical Pretreatment of Polymer Melts: Critical Aspects and New Rheological Investigations on a Linear and a Long-Chain Branched Polypropylene (Global Journal of Science Frontier Research, 2022)
This paper uses the pretext of commenting on the allegations contained in a paper published by M nstedt regarding this author s work on the shear-refinement of linear polymers to explain the difference between his model of polymer interactions the new school paradigm of polymer physics and the old school molecular dynamics paradigm defended by its guardians including M nstedt in this instance It is true that shear-refinement for linear polymers is not explained by the currently accepted models of rheology whereas it has received a partial explanation for branched polymers M nstedt concluded that shear-refinement effects can only be observed for long chain branched LCB polymers and that linear chain polymers cannot do so He suggested that the many results showing apparent successful shearrefinement in our work were probably artifacts or due to lacking measurements of the molecular weight before and after our shear-refinement treatments We show in this paper that M nstedt has not been genuine in his quotations of our work by incorrectly reporting the results and the procedures by muting important details and by making amalgams between different types of experiments he drew wrong conclusions that could possibly misrepresent more than inform the reader about the content of our work on the instability of the entanglement state The experimental reality of the instability of the entanglements should be debated in a straightforward scientific way without deception of the facts because its consequences if validated require a shift toward a new paradigm in polymer physics a new understanding of entanglements and of visco-elasticity nothing less We address in this publication the following issues - There is no good reason to doubt and attempt to disqualify the results on the shear-induced melt instability of linear polymers designated disentanglement in our work shear-refinement by Munstedt M nstedt s misquotes were corrected and their implications refuted - M nstedt used the classical topological description of long chain branched LCB polymers to support his opinion that linear chain polymers cannot qualify to successfully induce shear-refinement effects We argued that although LCBs and linear chains are architecturally different the true cause for shear-refinement must be found elsewhere and we pointed to the dynamic free volume as one of the causes of the melt instability triggering a reduction of viscosity LCB polymers have inherently more dynamic free volume than the linear polymers a positive attribute for shear-refinement but both architectures can support a substantial enhancement of dynamic free volume by melt Rheo-Fluidizing manipulation not just the LCB type The dynamic free volume is quantified by the Grain-Field Statistics model of the interactions but not by the molecular dynamic models - The reluctance to accept the melt instability experimental results by M nstedt was perhaps motivated by the lack of molecular dynamic models arguments to comprehend them - The discovery of the instability of the entanglement network triggers the necessity to understand entanglements differently - We briefly introduce the general principles underlying the Grain-Field Statistical model of interactive coupling of dissipative systems that we believe could become the basis for a new paradigm in polymer physics beyond the current limitations of the molecular dynamic models Rouse and reptation that have dominated our academic interpretation of the deformation of macromolecular chains but fail to construe new experimental evidence e g Sustained-Orientation the TLL transition